Tinjauan Atas Prosedur Pengelolaan Persediaan Bahan Baku Pada CV IDS - Pardede, Robert Pius; Aluna, Putri Fadella Ari (Jurnal Aplikasi Bisnis Kesatuan, 2023)
Inventory management is goods or materials stored in a company that are related to the production process or provision of services, as spare parts or goods that are resold. Inventory can include service costs such as wages and other HR costs directly involved in providing services as well as indirect production allocations. Raw material inventory is the amount of goods or materials available in a company or organization as input in the production or operational process. The purpose of preparing this Final Assignment is to review raw material inventory management procedures consisting of receiving, storing and dispensing raw material activities implemented by CV IDS. The results of this review show that the raw material inventory management procedures at CV IDS have been implemented well. In the procedure for receiving raw materials, the company requires purchase order (PO) and receipt report (RR) documents. And for raw material disbursement procedures, companies need a raw material disbursement book that is separate from the raw material receipt book.   Keywords: raw material inventory, raw material receiving, raw material storage, raw material dispensing.